KEMAMPUAN BERPIKIR KRITIS MELALUI PEMBELAJARAN MATEMATIKA DENGAN PROBLEM BASED LEARNING - Berta Apriza (Eksponen, 2019)
Education functions to upgrading, forming, character and develop civilization nation. Having the ability to think and actions to effective and creative in the realm of abstract and concrete can be used as self development independently. Students need to armed with critical thinking skills, systematic, logical, creative, and cooperate effectively to obtain, choose, and manage an information. Mathematics learning is directed to develop critical thinking skills and discussed open and objective because mathematics having strong and structure clear and links between the concept of the one with another concept. By analyzing learning needs of mathematics, formulate and designed a learning programs, choose a strategies and evaliated them correctly to get good results. The ability critical thinking is very important in studying new matter and that known way, and learn to ask effectively and reach a conclusion consistent with the facts. Mathematic learning with problem based learning is the concept of better used activity of the student during learning. In accordance with statements from Westwood (2008: 31) stated that PBL: 1) propel oneself directly in learning, 2) prepared students to critical thinking and analytical, 3) give opportunity to students to identify, find and use numerous this approuch in should think, 4) is the learning is very closely related to the real world and motivate students, 5) involving activeness in integrating information and skills of various the discipline, and 6) knowledge and strategy by the possibility of will be maintained and tranferred to the learning situation other, improve the ability to communicate and the social skills needed to cooperation and teamwork. By chance the learning process as an alternative in solving mathematical problems with using the ability critical think an to cultivate the scientific attitude of student.